2021
DOI: 10.3390/biology10080714
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Genetic Analysis of DGAT2 Mutations and Gene Expression Patterns in Human Cancers

Abstract: DGAT2 is a transmembrane protein encoded by the DGAT2 gene that functions in lipid metabolism, triacylglycerol synthesis, and lipid droplet regulation. Cancer cells exhibit altered lipid metabolism and mutations in DGAT2 may contribute to this state. Using data from the Catalogue of Somatic Mutations in Cancer (COSMIC), we analyzed all cancer genetic DGAT2 alterations, including mutations, copy number variations and gene expression. We find that several DGAT2 mutations fall within the catalytic site of the enz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 47 publications
1
1
0
Order By: Relevance
“…This result is consistent with previous studies reported on yaks, sheep, and chickens(1,2,28). DGAT2 is expressed widely in a variety of tissues in animals(1,29,30). The high expression level of DGAT2 in fat tissue indicates an important function in the synthesis and storage of triglycerides…”
supporting
confidence: 93%
“…This result is consistent with previous studies reported on yaks, sheep, and chickens(1,2,28). DGAT2 is expressed widely in a variety of tissues in animals(1,29,30). The high expression level of DGAT2 in fat tissue indicates an important function in the synthesis and storage of triglycerides…”
supporting
confidence: 93%
“…So far, DGAT2 inhibition has not been attempted in a clinical setting but was reported as a well-tolerated therapeutic option for patients with nonalcoholic fatty liver disease [53]. In addition, DGAT2 mutations are associated with the phenotype of impaired muscle structure and function (e.g., Charcot-Marie-Tooth disease) in humans [54] and cellular transformation properties in several types of human cancer [55]. The findings of this study will add more insight in the application of DGAT inhibitor in risk prediction of several metabolic diseases and in phenotype identification according to their genotype match.…”
Section: Discussionmentioning
confidence: 99%
“…DGAT2, as a transmembrane protein, functions in lipid metabolism, especially in triacylglycerol (TG) synthesis. DGAT2 knocked out mice die after birth with a >90% reduction in TGs, which suggests that DGAT2 may act as the predominant enzyme for TG storage [ 58 , 59 ]. DGAT2 is also involved in the carotenoid synthesis, which may be important for yellow pigment deposition in yellow mutant rainbow trout [ 60 ].…”
Section: Discussionmentioning
confidence: 99%